A benzonitrile-terminated silaneyne resin, its preparation method and application
By preparing benzonitrile-terminated silaneyne resin, the problems of brittleness and poor interfacial bonding performance of silaneyne resin were solved, and high strength and heat resistance of fiber-reinforced composite materials were achieved.
Patent Information
- Application Number
- CN202511247905.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-09-03
AI Technical Summary
Silicon-containing aromatic resins are brittle after curing and have poor interfacial bonding with reinforcing fibers, resulting in low mechanical strength of fiber-reinforced composites.
A method for preparing benzonitrile-terminated silaneyne resin was adopted, which involved mixing alkyl magnesium chloride lithium chloride, diethynyl aromatic compounds, and halobenzonitrile compounds through Grignard reagent substitution reaction and polycondensation reaction to obtain a mixed solution of aryynyl magnesium chloride lithium chloride and phenylcyano magnesium chloride lithium chloride, which was then reacted with dichlorosilane derivatives to prepare benzonitrile-terminated silaneyne resin.
The interfacial bonding performance between the resin and the fiber was improved, and the prepared fiber-reinforced composite material has excellent heat resistance and good mechanical strength, with flexural strength and modulus reaching over 290 MPa and over 33 GPa.
Smart Images

Figure CN120795326B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resin materials technology, specifically relating to a benzonitrile-terminated silaneyne resin, its preparation method, and its application. Background Technology
[0002] Silicon-containing aromatic yne resins are novel organic-inorganic hybrid resins formed by introducing silicon into the molecular structure of polyaryl acetylene resins. They possess low dielectric constants and dielectric losses, along with excellent high-temperature ceramization properties, making them highly promising for applications in aerospace and electronic information fields. However, silicon-containing aromatic yne resins are brittle after curing and exhibit poor interfacial adhesion to reinforcing fibers, resulting in low mechanical strength in the prepared fiber-reinforced composites, which has become a bottleneck limiting their development. Therefore, improving the mechanical strength of silicon-containing aromatic yne resins has become a challenging problem in this field. Summary of the Invention
[0003] The purpose of this invention is to provide a benzonitrile-terminated silaneyne resin, its preparation method, and its applications. Fiber-reinforced composite materials prepared using the benzonitrile-terminated silaneyne resin provided by this invention exhibit excellent mechanical strength.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0005] This invention provides a benzonitrile-terminated silaneyne resin, wherein the benzonitrile-terminated silaneyne resin has the structural formula shown in Formula I:
[0006] Formula I,
[0007] In Formula I, R1 and R2 are independently methyl, ethyl, vinyl, or phenyl; Ar is independently aromatic diethynyl; R3 and R4 are end-capped groups, R3 is cyanophenyl or dicyanophenyl, and R4 is cyanophenyl, dicyanophenyl, or ethynylarylene-acetyynyl; n is a positive integer from 0 to 30.
[0008] This invention also provides a method for preparing the benzonitrile-terminated silanenyne resin described in the above technical solution, comprising the following steps:
[0009] (1) Alkyl magnesium chloride lithium chloride, diethynyl aromatic compounds, halobenzonitrile compounds and organic solvents are mixed and subjected to Grignard reagent substitution reaction to obtain a mixed solution of aryynyl magnesium chloride lithium chloride and phenylcyano magnesium chloride lithium chloride;
[0010] (2) The mixed solution of arylynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride obtained in step (1) is mixed with dichlorosilane derivative and subjected to polycondensation reaction to obtain benzonitrile-terminated silaneylynyl resin.
[0011] Preferably, the diethynyl aromatic compounds in step (1) include one or more of 2,7-diethynylfluorene, 3,6-diethynylfluorene, 2,6-diethynylfluorene, 3,6-diethynylcarbazole, 2,7-diethynylcarbazole, 2,6-diethynylcarbazole, 1,4-diethynylbenzene, 1,2-diethynylbenzene, and 1,3-diethynylbenzene; and the halobenzonitrile compounds include one or more of 3-chlorobenzonitrile, 4-chlorobenzonitrile, 3-bromobenzonitrile, 4-bromobenzonitrile, 2-chlorobenzonitrile, 2-bromobenzonitrile, 4-chlorobenzene-1,2-dinitrile, 3-chlorobenzene-1,2-dinitrile, 4-bromobenzene-1,2-dinitrile, and 3-bromobenzene-1,2-dinitrile.
[0012] Preferably, the alkyl magnesium lithium chloride in step (1) is isopropyl magnesium lithium chloride or tert-butyl magnesium lithium chloride.
[0013] Preferably, in step (1), the molar ratio of diethynyl aromatic compounds, halobenzonitrile compounds and alkyl magnesium chloride lithium chloride is (1.0~2.0):(1.0~2.0):(3.0~6.0).
[0014] Preferably, the temperature of the Grignard reagent displacement reaction in step (1) is ≤-10℃, and the time of the Grignard reagent displacement reaction is 2~6h.
[0015] Preferably, the dichlorosilane derivative in step (2) includes one or more of dimethyldichlorosilane, methylvinyldichlorosilane, methylphenyldichlorosilane, and phenylvinyldichlorosilane.
[0016] Preferably, the molar ratio of the diethynyl aromatic compound in step (1) to the dichlorosilane derivative in step (2) is (0.5~2.0):1.
[0017] Preferably, the temperature of the polycondensation reaction in step (2) is -20~20℃, and the time of the polycondensation reaction is 8~96h.
[0018] This invention also provides the application of the benzonitrile-terminated silaneyne resin described in the above technical solution or the benzonitrile-terminated silaneyne resin prepared by the preparation method described in the above technical solution in the fields of fiber-reinforced composite materials, aerospace and electronic information.
[0019] This invention provides a benzonitrile-terminated silaneyne resin, wherein the benzonitrile-terminated silaneyne resin has the structural formula shown in Formula I:
[0020] Formula I,
[0021] In Formula I, R1 and R2 are independently methyl, ethyl, vinyl, or phenyl; Ar is independently aromatic diacetylenyl; R3 and R4 are end-capping groups, where R3 is cyanophenyl or dicyanophenyl, and R4 is cyanophenyl, dicyanophenyl, or acetylenyl-arylene-acetylenyl; n is a positive integer from 0 to 30. This invention controls the specific structure of the benzonitrile-terminated silaneyne resin, which exhibits good interfacial adhesion to fiber-reinforced materials. The prepared fiber-reinforced composite material possesses excellent heat resistance and good mechanical strength. The results of the examples show that the fiber-reinforced composite material prepared from the benzonitrile-terminated silaneyne resin provided by this invention has a flexural strength above 290 MPa and a flexural modulus above 33 GPa. Attached Figure Description
[0022] Figure 1 The infrared spectrum of the benzonitrile-terminated silanenyne resin synthesized in Example 1;
[0023] Figure 2 The image shows the hydrogen nuclear magnetic resonance spectrum of the benzonitrile-terminated silaneyne resin synthesized in Example 1. Detailed Implementation
[0024] This invention provides a benzonitrile-terminated silaneyne resin, wherein the benzonitrile-terminated silaneyne resin has the structural formula shown in Formula I:
[0025] Formula I.
[0026] In this invention, in Formula I, R1 and R2 are independently methyl, ethyl, vinyl, or phenyl; and Ar is independently aromatic diethynyl, preferably. , , , , , , , or R3 is cyanophenyl or dicyanophenyl, R4 is cyanophenyl, dicyanophenyl or ethynylarylene-acetylenyl; n is a positive integer from 0 to 30.
[0027] As one embodiment, the structural formula of the benzonitrile-terminated silaneyne resin can be specifically as follows: , , or .
[0028] The benzonitrile-terminated silaneyne resin of the present invention has low viscosity, good solubility in organic solvents, and the cured product has excellent heat resistance. The benzonitrile-terminated silaneyne resin has good interfacial bonding performance with fiber-reinforced materials, and the prepared fiber-reinforced composite material has excellent mechanical strength.
[0029] This invention also provides a method for preparing the benzonitrile-terminated silanenyne resin described in the above technical solution, comprising the following steps:
[0030] (1) Alkyl magnesium chloride lithium chloride, diethynyl aromatic compounds, halobenzonitrile compounds and organic solvents are mixed and subjected to Grignard reagent substitution reaction to obtain a mixed solution of aryynyl magnesium chloride lithium chloride and phenylcyano magnesium chloride lithium chloride;
[0031] (2) The mixed solution of arylynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride obtained in step (1) is mixed with dichlorosilane derivative and subjected to polycondensation reaction to obtain benzonitrile-terminated silaneylynyl resin.
[0032] Unless otherwise specified, the present invention does not impose any special restrictions on the source of the raw materials, and commercially available products well known to those skilled in the art can be used.
[0033] This invention involves mixing alkyl magnesium chloride and lithium chloride, diethynyl aromatic compounds, halobenzonitrile compounds, and organic solvents, and then performing a Grignard reagent substitution reaction to obtain a mixed solution of aryynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride.
[0034] In this invention, the alkyl magnesium lithium chloride is preferably isopropyl magnesium lithium chloride or tert-butyl magnesium lithium chloride.
[0035] In this invention, the diacetylenyl aromatic compounds preferably include one or more of 2,7-diethynylfluorene, 3,6-diethynylfluorene, 2,6-diethynylfluorene, 3,6-diethynylcarbazole, 2,7-diethynylcarbazole, 2,6-diethynylcarbazole, 1,4-diethynylbenzene, 1,2-diethynylbenzene, and 1,3-diethynylbenzene. As one embodiment, the diacetylenyl aromatic compounds may specifically be a mixture of 1,3-diethynylbenzene, 1,3-diethynylbenzene and 2,7-diethynylfluorene in a molar ratio of 1:1, or a mixture of 1,3-diethynylbenzene and 3,6-diethynylcarbazole in a molar ratio of 1:1.
[0036] In this invention, the halobenzonitrile compounds preferably include one or more of 3-chlorobenzonitrile, 4-chlorobenzonitrile, 3-bromobenzonitrile, 4-bromobenzonitrile, 2-chlorobenzonitrile, 2-bromobenzonitrile, 4-chlorobenzene-1,2-dionitrile, 3-chlorobenzene-1,2-dionitrile, 4-bromobenzene-1,2-dionitrile and 3-bromobenzene-1,2-dionitrile.
[0037] In this invention, the preferred molar ratio of the diethynyl aromatic compound, the halobenzonitrile compound, and the alkyl magnesium chloride / lithium chloride is (1.0~2.0):(1.0~2.0):(3.0~6.0). As one embodiment, the molar ratio of the diethynyl aromatic compound, the halobenzonitrile compound, and the alkyl magnesium chloride / lithium chloride can be specifically 1.0:1.0:3.0, 1.0:1.0:4.0, 1.0:1.0:5.0, 1.0:1.0:6.0, 2.0:1.0:3.0, 2.0:1.0:4.0, 2.0:1.0:5.0, or 2.0:1.0:6.0. By controlling the molar ratio of the diethynyl aromatic compound, the halobenzonitrile compound, and the alkyl magnesium chloride / lithium chloride within the above range, this invention ensures sufficient reaction of the raw materials.
[0038] In this invention, the organic solvent preferably includes one or more of tetrahydrofuran, methyltetrahydrofuran, toluene, diethyl ether, and dioxane.
[0039] In this invention, the preferred method for mixing the alkyl magnesium chloride, lithium chloride, diethynyl aromatic compounds, halobenzonitrile compounds, and organic solvents is as follows: mixing the alkyl magnesium chloride, lithium chloride, and a portion of the organic solvent to obtain mixed solution A; mixing the diethynyl aromatic compounds, halobenzonitrile compounds, and the remaining organic solvent to obtain mixed solution B; and adding mixed solution B dropwise to mixed solution A at a temperature below -10°C.
[0040] In this invention, the concentration of alkyl magnesium chloride and lithium chloride in the mixed solution A is preferably 1~1.5 mol / L. As one embodiment, the concentration of alkyl magnesium chloride and lithium chloride in the mixed solution A can specifically be 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, or 1.5 mol / L.
[0041] In this invention, the concentration of halobenzonitrile compounds in the mixed solution B is preferably 0.5~1.5 mol / L. As one embodiment, the concentration of halobenzonitrile compounds in the mixed solution B can specifically be 0.5 mol / L, 0.6 mol / L, 0.65 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.3 mol / L, or 1.5 mol / L.
[0042] The present invention does not impose any special limitation on the dripping rate; any dripping rate known to those skilled in the art can be used.
[0043] In this invention, the mixing is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon.
[0044] In this invention, the temperature of the Grignard reagent displacement reaction is preferably ≤-10℃; the time of the Grignard reagent displacement reaction is preferably 2~6h. As one embodiment, the temperature of the Grignard reagent displacement reaction can specifically be -10℃, -15℃, or -20℃; the time of the Grignard reagent displacement reaction can specifically be 2h, 3h, 4h, 5h, or 6h. By controlling the temperature and time of the Grignard reagent displacement reaction within the above ranges, this invention ensures that the reaction proceeds fully.
[0045] In this invention, the Grignard reagent displacement reaction is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon.
[0046] After obtaining a mixed solution of arylynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride, the present invention mixes the mixed solution of arylynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride with a dichlorosilane derivative and carries out a polycondensation reaction to obtain a benzonitrile-terminated silaneyne resin.
[0047] In this invention, the dichlorosilane derivative preferably includes one or more of dimethyldichlorosilane, methylvinyldichlorosilane, methylphenyldichlorosilane, and phenylvinyldichlorosilane. As one embodiment, the dichlorosilane derivative may specifically be dimethyldichlorosilane, methylvinyldichlorosilane, or a mixture of methylvinyldichlorosilane and dimethyldichlorosilane in a molar ratio of 1:1.
[0048] In this invention, the preferred molar ratio of the diethynyl aromatic compound to the dichlorosilane derivative is (0.5~2.0):1. As one embodiment, the molar ratio of the diethynyl aromatic compound to the dichlorosilane derivative can specifically be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.5:1, or 2.0:1.
[0049] In this invention, the preferred method for mixing the mixed solution of aryynyl magnesium chloride and lithium chloride with phenylcyano magnesium chloride and lithium chloride and the dichlorosilane derivative is to add the dichlorosilane derivative dropwise to the mixed solution of aryynyl magnesium chloride and lithium chloride with phenylcyano magnesium chloride and lithium chloride at a temperature below 0°C.
[0050] The present invention does not impose any special limitation on the dripping rate; any dripping rate known to those skilled in the art can be used.
[0051] In this invention, the mixing is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon.
[0052] In this invention, the preferred temperature for the polycondensation reaction is -20 to 20°C; the preferred time for the polycondensation reaction is 8 to 96 hours. As one embodiment, the specific temperature for the polycondensation reaction can be -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, or 20°C; the specific time for the polycondensation reaction can be 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 55 hours, 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, 90 hours, 95 hours, or 96 hours. By controlling the temperature and time of the polycondensation reaction within the above ranges, this invention ensures that the reaction proceeds fully.
[0053] In this invention, the polycondensation reaction is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon.
[0054] After the polycondensation reaction is completed, the present invention preferably adds a terminator to the system after the polycondensation reaction, and then performs water washing, separation to obtain an organic phase, drying, filtration to obtain a filtrate, and vacuum distillation to obtain a benzonitrile-terminated silaneyne resin.
[0055] In this invention, the terminating agent preferably includes one or more of water, acetic acid, and hydrochloric acid.
[0056] The present invention does not impose any special limitations on the amount of the terminator added, the water washing, the separation of the organic phase, the drying, the filtration to obtain the filtrate, and the vacuum distillation. Any technical solution known to those skilled in the art can be used.
[0057] This invention uses alkyl magnesium chloride and lithium chloride to dehalogenate benzonitrile compounds, introducing benzonitrile groups into the resin system. This overcomes the problem that traditional alkyl Grignard reagents will undergo oxidation reactions with cyano groups. At the same time, the aryynyl group will also undergo Grignard reagent substitution reactions with alkyl magnesium chloride and lithium chloride. After adding dichlorosilane derivatives, an aryynyl resin containing benzonitrile is obtained. The synthesis process is simple and efficient.
[0058] This invention also provides the application of the benzonitrile-terminated silaneyne resin described in the above technical solution or the benzonitrile-terminated silaneyne resin prepared by the preparation method described in the above technical solution in the fields of fiber-reinforced composite materials, aerospace and electronic information.
[0059] The cured product of the benzonitrile-terminated silaneyne resin provided by this invention has excellent heat resistance. The benzonitrile-terminated silaneyne resin and the reinforcing material have good interfacial bonding performance. The prepared composite material has excellent mechanical strength and can meet the requirements of high temperature resistant resin in the aerospace and electronic information fields.
[0060] This invention does not impose any special limitations on the application described herein; any technical solution known to those skilled in the art can be used.
[0061] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0062] Example 1
[0063] A benzonitrile-terminated silanenyne resin has the following structural formula:
[0064] ;
[0065] The preparation method of the benzonitrile-terminated silaneyne resin is as follows: (1) Under the protection of dry nitrogen, isopropyl magnesium chloride lithium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 11.83 g (0.065 mol) 3-bromobenzonitrile, 16.38 g (0.13 mol) 1,3-diethynylbenzene and 100 mL tetrahydrofuran are mixed to obtain a mixed solution B (the concentration of 3-bromobenzonitrile in mixed solution B is 0.65 mol / L); mixed solution B is added dropwise to mixed solution A, and the temperature during the dropwise addition is not higher than -10℃. After the dropwise addition is completed, the mixture is reacted at -15℃ for 3 h to obtain a mixed solution of aromatic diethynyl magnesium chloride lithium chloride and benzonitrile magnesium chloride lithium chloride.
[0066] (2) Under dry nitrogen protection, 18.33 g (0.13 mol) of methyl vinyl dichlorosilane was added dropwise to the mixed solution of aromatic diethynyl magnesium chloride and lithium chloride and benzonitrile magnesium chloride and lithium chloride obtained in step (1). The temperature during the dropwise addition was not higher than 0℃. After the dropwise addition was completed, the mixture was reacted at -5℃ for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was distilled under reduced pressure to obtain a brown viscous liquid benzonitrile-terminated silaneyne resin.
[0067] Structural characterization of the benzonitrile-terminated silaneyne resin prepared in Example 1: 1 1H-NMR (CDCl3, 600MHz, ppm): δ7.25~7.89ppm represents the chemical shifts of the benzene ring hydrogens, δ6.09~6.26ppm represents the chemical shifts of the vinyl hydrogens, and δ3.08ppm represents the chemical shifts of the terminal alkyne hydrogens. (1H NMR spectroscopy analysis) 1 H-NMR was performed using an Avance 600 high-resolution Fourier transform nuclear magnetic resonance spectrometer from Bruker, USA, at a working frequency of 600 MHz, with CDCl3 as the solvent and TMS as the internal standard.
[0068] FTIR (KBr tablet coating, cm) -1 3290cm -1 The characteristic absorption peak of -C≡CH is at 2231 cm⁻¹. -1 The characteristic absorption peak of -C≡N is at 2156 cm⁻¹. -1 The characteristic absorption peak of -C≡C- is at 1650 cm⁻¹. -1 The characteristic absorption peak of vinyl-C=C- is 1600~1450 cm⁻¹. -1 The peaks represent characteristic absorption peaks of the benzene ring. Fourier transform infrared spectroscopy (FTIR) was performed using a Nicolet 6700 Fourier transform infrared spectrometer (NICOLET, USA), KBr pellet method, scanning range 4000–400 cm⁻¹. -1 Resolution 0.04cm -1 The number of scans was 32.
[0069] Example 2
[0070] A benzonitrile-terminated silanenyne resin has the following structural formula:
[0071] ;
[0072] The preparation method of the benzonitrile-terminated silaneyne resin is as follows: (1) Under the protection of dry nitrogen, isopropyl magnesium chloride lithium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 11.83 g (0.065 mol) 3-bromobenzonitrile, 8.19 g (0.065 mol) 1,3-diethynylbenzene, 13.91 g (0.065 mol) 2,7-diethynylfluorene and 100 mL tetrahydrofuran are mixed to obtain a mixed solution B (the concentration of 3-bromobenzonitrile in mixed solution B is 0.65 mol / L); mixed solution B is added dropwise to mixed solution A, and the temperature during the dropwise addition is not higher than -10℃. After the dropwise addition is completed, the mixture is reacted at -15℃ for 3 h to obtain a mixed solution of aromatic diethynyl magnesium chloride lithium chloride and benzonitrile magnesium chloride lithium chloride.
[0073] (2) Under dry nitrogen protection, 25.15 g (0.195 mol) of dimethyldichlorosilane was added dropwise to the mixed solution of aromatic diethynyl magnesium chloride and lithium chloride and benzonitrile magnesium chloride and lithium chloride obtained in step (1). The temperature during the dropwise addition was not higher than 0℃. After the dropwise addition was completed, the mixture was reacted at -5℃ for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was removed by vacuum distillation to obtain a brownish-red viscous liquid benzonitrile-terminated silaneyne resin.
[0074] Structural characterization of the benzonitrile-terminated silaneyne resin prepared in Example 2: 1¹H-NMR (CDCl₃, 600MHz, ppm): δ6.98~7.69ppm represents the chemical shift of hydrogen on the benzene ring, δ3.84ppm represents the chemical shift of -CH₂- hydrogen on the fluorene ring, and δ0.43ppm represents the chemical shift of hydrogen on the silanyl methyl group.
[0075] FTIR (KBr tablet coating, cm) -1 ): 2230cm -1 The characteristic absorption peak of -C≡N is at 2140 cm⁻¹. -1 The characteristic absorption peak of -C≡C- is 1620~1450 cm⁻¹. -1 This is a characteristic absorption peak of the benzene ring.
[0076] Example 3
[0077] A benzonitrile-terminated silanenyne resin has the following structural formula:
[0078] ;
[0079] The preparation method of the benzonitrile-terminated silaneyne resin is as follows: (1) Under the protection of dry nitrogen, isopropyl magnesium chloride lithium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 9.00 g (0.065 mol) 3-chlorobenzonitrile, 8.19 g (0.065 mol) 1,3-diethynylbenzene, 13.98 g (0.065 mol) 3,6-diethynylcarbazole and 50 mL tetrahydrofuran are mixed to obtain a mixed solution B (the concentration of 3-chlorobenzonitrile in mixed solution B is 1.3 mol / L); mixed solution B is added dropwise to mixed solution A, and the temperature during the dropwise addition is not higher than -10℃. After the dropwise addition is completed, the mixture is reacted at -15℃ for 3 h to obtain a mixed solution of aromatic diethynyl magnesium chloride lithium chloride and benzonitrile magnesium chloride lithium chloride.
[0080] (2) Under dry nitrogen protection, 18.33 g (0.13 mol) of methyl vinyl dichlorosilane was added dropwise to the mixed solution of aromatic diethynyl magnesium chloride and lithium chloride and benzonitrile magnesium chloride and lithium chloride obtained in step (1). The temperature during the dropwise addition was not higher than 0℃. After the dropwise addition was completed, the mixture was reacted at -5℃ for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was removed by vacuum distillation to obtain a dark brown viscous liquid benzonitrile-terminated silaneyne resin.
[0081] Structural characterization of the benzonitrile-terminated silaneyne resin prepared in Example 3: 1¹H-NMR (CDCl₃, 600MHz, ppm): δ7.24~8.25ppm are the chemical shifts of hydrogen atoms on the benzene ring, δ6.12~6.53ppm are the chemical shifts of hydrogen atoms on the vinyl group, δ3.08ppm are the chemical shifts of hydrogen atoms on the terminal alkyne group, and δ0.43ppm are the chemical shifts of hydrogen atoms on the silanyl group.
[0082] FTIR (KBr tablet coating, cm) -1 ): 3406cm -1 The characteristic absorption peak of -NH- is at 3280 cm⁻¹. -1 The characteristic absorption peak of -C≡CH is at 2235 cm⁻¹. -1 The characteristic absorption peak of -C≡N is at 2153 cm⁻¹. -1 The characteristic absorption peak of -C≡C- is at 1660 cm⁻¹. -1 The characteristic absorption peak of -C=C- in vinyl groups is 1620~1450 cm⁻¹. -1 This is a characteristic absorption peak of the benzene ring.
[0083] Example 4
[0084] A benzonitrile-terminated silanenyne resin has the following structural formula:
[0085] ;
[0086] The preparation method of the benzonitrile-terminated silaneyne resin is as follows: (1) Under dry nitrogen protection, isopropyl magnesium chloride lithium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 11.83 g (0.065 mol) 3-bromobenzonitrile, 8.19 g (0.065 mol) 1,3-diethynylbenzene, 13.91 g (0.065 mol) 2,7-diethynylfluorene and 50 mL tetrahydrofuran are mixed to obtain a mixed solution B (the concentration of 3-bromobenzonitrile in mixed solution B is 1.3 mol / L); mixed solution B is added dropwise to mixed solution A, and the temperature during the dropwise addition is not higher than -10℃. After the dropwise addition is completed, the mixture is reacted at -15℃ for 3 h to obtain a mixed solution of aromatic diethynyl magnesium chloride lithium chloride and benzonitrile magnesium chloride lithium chloride;
[0087] (2) Under dry nitrogen protection, 9.17 g (0.065 mol) of methylvinyl dichlorosilane and 8.39 g (0.065 mol) of dimethyl dichlorosilane were added dropwise to the mixed solution of aromatic diethynyl magnesium chloride and lithium chloride and benzonitrile magnesium chloride and lithium chloride obtained in step (1). The temperature during the dropwise addition was not higher than 0℃. After the dropwise addition was completed, the mixture was reacted at -5℃ for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was removed by vacuum distillation to obtain a brownish-red viscous liquid benzonitrile-terminated silaneyne resin.
[0088] Structural characterization of the benzonitrile-terminated silaneyne resin prepared in Example 4: 1 ¹H-NMR (CDCl₃, 600MHz, ppm): δ7.01~7.81ppm are the chemical shifts of hydrogen on the benzene ring, δ6.12~6.53ppm are the chemical shifts of hydrogen on the vinyl group, δ3.84ppm are the chemical shifts of -CH₂- hydrogen on the fluorene ring, δ3.02ppm are the chemical shifts of hydrogen on the terminal alkyne group, and δ0.43ppm are the chemical shifts of hydrogen on the silanyl group.
[0089] FTIR (KBr tablet coating, cm) -1 ): 3291cm -1 The characteristic absorption peak of -C≡CH is at 2234 cm⁻¹. -1 The characteristic absorption peak of -C≡N is at 2144 cm⁻¹. -1 The characteristic absorption peak of -C≡C- is at 1662 cm⁻¹. -1 The characteristic absorption peak of vinyl-C=C- is 1620~1450 cm⁻¹. -1 This is a characteristic absorption peak of the benzene ring.
[0090] Comparative Example 1
[0091] A silane-containing resin has the following structural formula:
[0092] ;
[0093] The preparation method of the silicon-containing aromatic yne resin is as follows: (1) Under the protection of dry nitrogen, ethyl magnesium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 20.48 g (0.16 mol) 1,3-diethynylbenzene and 50 mL tetrahydrofuran are mixed to obtain a mixed solution B; at -10℃, the mixed solution B is added dropwise to the mixed solution A. After the addition is completed, the mixture is reacted at -15℃ for 3 h to obtain an aromatic diaethynyl magnesium chloride solution.
[0094] (2) Under dry nitrogen protection, 15.51 g (0.11 mol) of methyl vinyl dichlorosilane was added dropwise to the aromatic diethynyl magnesium chloride solution obtained in step (1) at 0 °C. After the addition was completed, the mixture was reacted at -5 °C for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was removed by vacuum distillation to obtain a brown viscous liquid containing silane aromatic resin.
[0095] Structural characterization of the silyl arylene resin prepared in Comparative Example 1: 1¹H-NMR (CDCl₃, 600MHz, ppm): δ 7.12~7.63ppm are the chemical shifts of hydrogen atoms on the benzene ring, δ 6.00~6.45ppm are the chemical shifts of hydrogen atoms on the vinyl group, and δ 3.08ppm are the chemical shifts of hydrogen atoms at the terminal alkyne.
[0096] FTIR (KBr tablet coating, cm) -1 ): 3291cm -1 The characteristic absorption peak of -C≡CH is at 2130 cm⁻¹. -1 The characteristic absorption peak of -C≡C- is at 1653 cm⁻¹. -1 The characteristic absorption peak of -C=C- on vinyl groups is 1620~1450 cm⁻¹. -1 This is a characteristic absorption peak of the benzene ring.
[0097] Comparative Example 2
[0098] A phenylcyano-terminated silaneyne resin has the following structural formula:
[0099] ;
[0100] The preparation method of the benzonitrile-terminated silaneyne resin is as follows: (1) Under dry nitrogen protection, isopropyl magnesium chloride lithium chloride and 250 mL tetrahydrofuran are mixed to obtain a mixed solution A with a concentration of 1.3 mol / L; 11.83 g (0.065 mol) 3-bromobenzonitrile, 16.38 g (0.13 mol) 1,3-diethynylbenzene and 100 mL tetrahydrofuran are mixed to obtain a mixed solution B (the concentration of 3-bromobenzonitrile in mixed solution B is 0.65 mol / L); at -10℃, mixed solution B is added dropwise to mixed solution A. After the addition is completed, the mixture is reacted at -15℃ for 3 h to obtain a mixed solution of aromatic diethynyl magnesium chloride lithium chloride and benzonitrile magnesium chloride lithium chloride.
[0101] (2) Under dry nitrogen protection, 14.95 g (0.13 mol) of methyl dichlorosilane was added dropwise at 0 °C to the mixed solution of aromatic diethynyl magnesium chloride and lithium chloride and benzonitrile magnesium chloride and lithium chloride obtained in step (1). After the addition was completed, the mixture was reacted at -5 °C for 48 h. Then, 15 g (0.25 mol) of acetic acid was added. After washing with water until neutral, the organic phase was taken and dried with anhydrous sodium sulfate for 12 h. After separation by filtration, the filtrate was removed by vacuum distillation to obtain a brown viscous liquid benzonitrile-terminated silaneyne resin.
[0102] The benzonitrile-terminated silanenyne resin prepared in Comparative Example 2 1 H-NMR (CDCl3, 600MHz, ppm): δ7.17~7.84ppm are the chemical shifts of the benzene ring hydrogens, δ4.40~4.72ppm are the chemical shifts of the silicon hydrogens, and δ3.00ppm are the chemical shifts of the terminal alkyne hydrogens.
[0103] FTIR (KBr film coating, cm) -1 3296cm -1 The characteristic absorption peak of -C≡CH is at 2232 cm⁻¹. -1 The characteristic absorption peak of -C≡N is at 2156 cm⁻¹. -1 The characteristic absorption peaks are the overlap of -C≡C- with silane-hydrogen bonds, 1600~1450 cm⁻¹. -1 This is a characteristic absorption peak of the benzene ring.
[0104] The resins prepared in Examples 1-4 and Comparative Examples 1-2 were cured in air according to the following curing process: 140℃ / 2h, 160℃ / 2h, 180℃ / 2h, 210℃ / 2h, and 250℃ / 4h, yielding a dense, glossy black solid. The cured resin was then tested using a thermogravimetric analyzer (TGA) in a nitrogen atmosphere, with the 5% thermogravimetric temperature (T0) as the starting point. d5 ) and 800℃ residual rate (Y c800 The thermal stability of the resin was measured using the method described in Table 1.
[0105] Table 1. Thermal stability of resins after curing in Examples 1-4 and Comparative Examples 1-2.
[0106]
[0107] Composite materials were prepared using the resins prepared in Examples 1-4 and Comparative Examples 1-2. The preparation method was as follows: Quartz fiber cloth was cut into pieces with dimensions of 150mm × 100mm. A 50wt% resin-acetone solution was then uniformly impregnated into the quartz fiber cloth (impregnation temperature: room temperature; impregnation time: 30 min). Twelve layers of prepreg were neatly stacked together and treated in a 95℃ vacuum oven for 30 min to remove the solvent. Afterwards, the mixture was cured under pressure on a flat vulcanizing machine (140℃ / 2h, 160℃ / 2h, 180℃ / 2h, 210℃ / 2h, and 250℃ / 4h), with a pressure of 1.5 MPa. After curing, the composite material plates were cut to the standard dimensions required for the test (GB / T 1449-2005). According to GB / T... 2567-2008 The flexural strength and flexural modulus of the composite material were tested. The experimental loading rate was 2 mm / min. The test was conducted continuously until the specimen failed. The test results of the flexural mechanical properties are shown in Table 2.
[0108] Table 2 Flexural strength and flexural modulus of composite materials
[0109]
[0110] As can be seen from Tables 1 and 2, the cured resins of the examples exhibit better thermal properties compared to Comparative Example 1. The composite materials of these examples show significantly improved strength and modulus compared to Comparative Example 1. While the resins prepared in the examples show slightly lower heat resistance compared to the resins of Comparative Example 2, the mechanical properties of their composite materials are significantly improved.
[0111] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A benzonitrile-terminated silanenyne resin, characterized in that, The benzonitrile-terminated silanenyne resin has the structural formula shown in Formula I: Formula I, In Formula I, R1 and R2 are independently methyl, ethyl, vinyl, or phenyl; Ar is independently aromatic diethynyl; R3 and R4 are end-capped groups, R3 is cyanophenyl or dicyanophenyl, and R4 is cyanophenyl, dicyanophenyl, or ethynylarylene-acetyynyl; n is a positive integer from 0 to 30.
2. The method for preparing the benzonitrile-terminated silanenyne resin according to claim 1, characterized in that, Includes the following steps: (1) Alkyl magnesium chloride lithium chloride, diethynyl aromatic compounds, halobenzonitrile compounds and organic solvents are mixed and subjected to Grignard reagent substitution reaction to obtain a mixed solution of aryynyl magnesium chloride lithium chloride and phenylcyano magnesium chloride lithium chloride; (2) The mixed solution of arylynyl magnesium chloride and lithium chloride and phenylcyano magnesium chloride and lithium chloride obtained in step (1) is mixed with dichlorosilane derivative and subjected to polycondensation reaction to obtain benzonitrile-terminated silaneylynyl resin.
3. The preparation method according to claim 2, characterized in that, The diethynyl aromatic compounds in step (1) include one or more of 2,7-diethynylfluorene, 3,6-diethynylfluorene, 2,6-diethynylfluorene, 3,6-diethynylcarbazole, 2,7-diethynylcarbazole, 2,6-diethynylcarbazole, 1,4-diethynylbenzene, 1,2-diethynylbenzene, and 1,3-diethynylbenzene; the halobenzonitrile compounds include one or more of 3-chlorobenzonitrile, 4-chlorobenzonitrile, 3-bromobenzonitrile, 4-bromobenzonitrile, 2-chlorobenzonitrile, 2-bromobenzonitrile, 4-chlorobenzene-1,2-dinitrile, 3-chlorobenzene-1,2-dinitrile, 4-bromobenzene-1,2-dinitrile, and 3-bromobenzene-1,2-dinitrile.
4. The preparation method according to claim 2, characterized in that, The alkyl magnesium lithium chloride in step (1) is isopropyl magnesium lithium chloride or tert-butyl magnesium lithium chloride.
5. The preparation method according to claim 2, characterized in that, In step (1), the molar ratio of diethynyl aromatic compounds, halobenzonitrile compounds, and alkyl magnesium chloride and lithium chloride is (1.0~2.0):(1.0~2.0):(3.0~6.0).
6. The preparation method according to claim 2, characterized in that, In step (1), the temperature of the Grignard reagent displacement reaction is ≤-10℃, and the time of the Grignard reagent displacement reaction is 2~6h.
7. The preparation method according to claim 2, characterized in that, The dichlorosilane derivatives in step (2) include one or more of dimethyldichlorosilane, methylvinyldichlorosilane, methylphenyldichlorosilane, and phenylvinyldichlorosilane.
8. The preparation method according to claim 2, characterized in that, The molar ratio of the diethynyl aromatic compound in step (1) to the dichlorosilane derivative in step (2) is (0.5~2.0):
1.
9. The preparation method according to claim 2, characterized in that, The temperature of the polycondensation reaction in step (2) is -20~20℃, and the reaction time is 8~96h.
10. The application of the benzonitrile-terminated silaneyne resin according to claim 1 or the benzonitrile-terminated silaneyne resin prepared by any one of claims 2 to 9 in the fields of fiber-reinforced composite materials, aerospace and electronic information.
Citation Information
Patent Citations
Synthetic method of NH-1, 2, 3-triazole compound
CN103288765A
High-modulus silicon-containing aryne resin, composite material and preparation method of high-modulus silicon-containing aryne resin
CN113354821A